Role of husband's attitude towards the usage of contraceptives for unmet need of family planning among married women of reproductive age in Pakistan - Muhammad Farhan Asif; Zahid Pervaiz; Jawad Rahim Afridi; Ghulam Abid; Zohra S. Lassi (BMC, 2021)
Abstract Background Family planning services deliver a wide range of benefits to the well-being of females and the community. It can curtail the risk of maternal and neonatal mortality through the reduction in abortions and pregnancies. The government of Pakistan has been struggling to convince people about the usefulness of family planning programs. However, different factors related to social norms, values, and culture are important to determine the success of these programs. One such factor is the patriarchal structure of Pakistani society where most of the household decisions are made by men. The objective of this research is to examine the role of the husband's attitude towards the usage of contraceptives for the unmet need of family planning (UMNFP) among married women of reproductive age (MWRA) in Pakistan. Method The dataset of Pakistan Demographic and Health Survey 2017-18 is utilized to examine the role of the husband's attitude towards the usage of contraceptives in UMNFP among MWRA in Pakistan. Results The UMNFP was considerably lower among MWRA between 40 years and above compared to women 15-19 years. The odds of UMNFP were higher among women and men who were educated up to the primary level compared to those with no education. Odds of UMNFP were higher among women from the poor wealth quintile compared to the poorest wealth quintile; similarly, it was significantly lower among women who were from the richer and the richest wealth quintile compared to the poorest wealth quintile. The odds of UMNFP were lower among women who were employed compared to those who were not employed. Lastly, the odds of UMNFP were higher among women whose husbands opposed to using contraceptives, who perceived that there was a religious prohibition for such use and when a decision on the contraception use was solely made by the husband. Conclusions Husband's attitude towards the usage of contraceptives is an important predictor of UMNFP. Liaising with the community and religious leaders to persuade people particularly men about the usefulness of family planning programs and encouraging men to understand their women's say in using contraceptives should be encouraged.